A pediatric case of fever of unknown origin and pericarditis associated with actinomyces pneumonia. (2022) - Alexanian, Ara Albert; Brager, Rhobe; Mendoza, Maria Concepcion; Keosheyan, Rhonda
Abstract: We describe a rare case of Actinomyces meyeri pneumonia in a pediatric patient. Our patient was admitted twice for recurrent pericarditis in the setting of persistent fevers, initially thought to be secondary to Coxsackie B virus. She was treated with colchicine and ibuprofen, as well as a short course of oral steroids. Patient was admitted a third time for acute respiratory failure and was found to have a large right empyema and pleural effusion requiring chest tube placement. After extensive multi-specialty workup, A. meyeri was isolated from chest tube culture. Patient's intravenous (IV) antibiotics were subsequently narrowed to ampicillin, and she was discharged.